Sociotechnical Model of Ship Organization Effectiveness - Toni Bielić; Robert Mohović; Renato Ivče (Promet - Traffic&Transportation, 2012)
This article investigates the possibility of optimizing the organization of a ship as a highly complex technical system. In this sense, the existing relationship between technology and the human as a user is considered. Using the socio-technical approach the aim is to identify the weaknesses in the existing technological and organizational ship’s system. Based on research conducted on the navigation simulator, socio-technical components that affect the safety of navigation have been observed. By subsequent comparative analyses of the implementation of technical solutions in accordance with the human requirements certain solutions are proposed and conclusions made.KEY WORDS: socio-technical model, ship organization, safety, effectiveness, technology indulgence, control systems, automation